2014
DOI: 10.1136/amiajnl-2014-002820
|View full text |Cite
|
Sign up to set email alerts
|

Can older people remember medication reminders presented using synthetic speech?

Abstract: Reminders are often part of interventions to help older people adhere to complicated medication regimes. Computer-generated (synthetic) speech is ideal for tailoring reminders to different medication regimes. Since synthetic speech may be less intelligible than human speech, in particular under difficult listening conditions, we assessed how well older people can recall synthetic speech reminders for medications. 44 participants aged 50–80 with no cognitive impairment recalled reminders for one or four medicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…We use two sets of semantic fluency test data produced by English and Korean native speakers. The English data were collected from the studies Wolters et al (2014) and Iveson (2015), whereas the Korean data were collected by members of the NLP*CL lab, KAIST, South Korea for a study of acoustic and linguistic structure of category fluency data including Wolters et al (2016). We outline the details of each dataset below.…”
Section: Discussionmentioning
confidence: 99%
“…We use two sets of semantic fluency test data produced by English and Korean native speakers. The English data were collected from the studies Wolters et al (2014) and Iveson (2015), whereas the Korean data were collected by members of the NLP*CL lab, KAIST, South Korea for a study of acoustic and linguistic structure of category fluency data including Wolters et al (2016). We outline the details of each dataset below.…”
Section: Discussionmentioning
confidence: 99%
“…As some studies have demonstrated (Craig and Schroeder, 2017, 2019) perception improves when synthetic voices have better sound quality. Current technology has considerably improved in the past years, and synthetic voices now sound more intelligible and natural (Wolters et al, 2014). Some companies are now using Artificial Intelligence (A.I.)…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Due to artificiality, listeners need more cognitive resources to process synthetic voices, and therefore, the cognitive effort is greater than when processing human voices. This artificiality affects the recall process (Wolters et al, 2014). However, this extensive use of cognitive resources could be beneficial.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The success of reminder use has been variable, and the analysis of reminder use is based on a research methodology that relies on self-reported adherence as the primary factor for the validation of medication use [ 19 - 23 ]. Self-reported adherence can be an overestimated and biased account of medication adherence [ 24 ].…”
Section: Introductionmentioning
confidence: 99%